Constitution of the Pt-Cr-Nb system - Mulaudzi, Fulufhelo Marandela Lloyd (My University, 2009)
Superalloys based on platinum-group metals (PGMs) are being developed for high temperature applications. Currently, the optimum alloy is Pt84:Al11:Ru2:Cr3, and work is ongoing. Niobium is a possible addition to increase the melting point, but limited phase diagram data are available. Although work has been done on the Pt-Al-Nb system, there are no reported data for Pt-Cr-Nb. This is a study of the Pt-Cr-Nb system. As-cast samples of the Pt-Cr-Nb ternary system were investigated using scanning electron microscopy with energy-dispersive X-ray spectroscopy, and X-ray diffraction. The results were used to plot a solidification projection and all binary phases extended into the ternary, except for α´Pt, which was not identified in this investigation. The extensions of the binary phases were: (Cr) ~2 at.% Nb; (Pt) ~24 at.% Nb and 65 at.% Cr; (Nb): ~12 at.% Pt and ~17 at.% Cr; ~NbPt2: ~20 at.% Cr; ~NbCr2: ~18 at.% Pt; ~Cr3Pt: ~10 at.% Nb; ~βNbPt3: ~4 at.% Cr and ~Nb1-XPt1+X: ~13 at.% Cr. Five ternary phases were identified: τ1:~Nb17:Cr64:Pt19; τ2:~Nb28:Cr55:Pt17; τ3:~Nb30:Cr30:Pt40; τ4:~Nb45:Cr27:Pt28 and τ5:~Nb40:Cr18:Pt42. The liquidus surface was derived using the binary phase diagrams, identified primary phases, solidification sequences and the solidification projection, together with the eutectic compositions. Nineteen ternary invariant reactions were identified. Hardness measurements were made on all samples, and also toughness and fracture toughness were deduced. Alloys with (Pt) and ~NbPt2 were ductile with reasonable hardness. Alloys containing (Cr), (Nb), ~Cr3Pt, ~NbCr2, ~Nb3Pt and ~Nb2Pt were extremely brittle with cracks, whereas alloys containing ~βNbPt3 and ~Nb1-XPt1+X phases were slightly brittle.
Keywords: Phase diagram; Nb-Cr-Pt system; Scanning electron microscopy; X-ray diffraction